Factores ambientales y su incidencia en la bronquitis aguda en niños menores de 7 años que asisten al Hospital IEES Milagro octubre 2018 – abril 2019 - Mariduena Pinos, Gabriela Cecibel (2019)
This research project is developed with the purpose of discovering which are the main environmental factors that produce acute bronchitis in children under 7 years, which the general objective, to determine which are the environmental factors that cause acute bronchitis children, taking as a focus to children younger than 7 years old who attend the IEES miracle hospital to develop the research project, we used inductive, qualitative and quantitative methodology which allowed us to collect information, and achieve favorable results, which we obtained favorable results for the project, because it was concluded that in order to prevent the proliferation of acute bronchitis, the necessary prevention measures must be taken and the risk of exposure to environmental factors that cause acute bronchitis must be reduced. The proactive work that we carry out in the end is to propose educational talks about preventive measures so that it allows us to reduce the number of cases of acute bronchitis in the IEES miracle hospital, which resulted in good results as a result of the hard work that was carried out.